EFL Students’ Responses on Learning Academic Essays in Indonesian Higher Education - Syayid Sandi Sukandi; Riny Dwitya Sani (AT-TA'LIM, 2017)
This article provides investigation on EFL students’ responses related to learning writing academic essays in the context of higher education in one of private universities in Indonesia. The gap that is studied in this research is related to rarity of English writing instructors in identifying what their students’ responses towards their learning process after completing an essay writing course and how the responses present significant ideas on improving writing instructors’ pedagogical practices in writing classrooms. Scope of this research is teaching and learning English writing within the context of English as a foreign language. Field of this research is English composition studies. This research applies a quantitative non-experiment design, with descriptive as its method and questionnaire as its instruments. Findings show that students view English writing in neutral attitude; meanwhile, writing thesis statement in an academic essay is the most difficult part to write (40.59% of all respondents), and grammar and punctuation in writing essay is the most difficult aspect of essay writing (51.96% of all respondents). In brief, this research shows that recognising which aspect of the academic essay that is difficult for the students and which element is hard for them is crucial for adjusting pedagogical practices for English writing instructors and improving quality of their teaching gradually in Indonesia